Effects of Immigration on Labour Markets and Government Budgets - An Overview - Willi Leibfritz; Paul O'Brien; Jean-Christophe Dumont (Center for Economic Studies and ifo Institute (CESifo), 2003)
The paper provides an overview on recent trends of immigration in OECD countries and on the possible effects of immigration on labour markets and government budgets. It also discusses migration policies from an economic point of view. By bringing together a bulk of international literature on labour market and fiscal effects of migration in a systematic way it provides a framework for assessing the economic effects of migration and improving the knowledge base for migration policies.
Keywords: 330; migration; labour markets; fiscal effects of migration